PROSPECTS FOR THE USE OF BEE POLLEN IN THE PRODUCTION OF DESSERT DAIRY PRODUCTS - Ekaterina Nikolaevna Holodova; Arkady Viktorovich Kazantsev (Современная наука и инновации)
Products of beekeeping possess a wide range of biological properties and have positive a cart effect on a human body. As a food component for enrichment of finished goods the bee pollen which is let out in accordance with GOST 28887-90 is chosen. Bee pollen represents the vitamin and mineral, power complex balanced by the nature.